Evaluation of tumour-associated macrophages and colony-stimulating factor-1 expression in invasive breast carcinoma and their association with prognostic parameters - Sediqi, Mohammad Faiq; Ahmad Affandi, Khairunisa; Muhammad, Siti Aeshah @ Naznin; A Talib, Norlelawati; Che Alhadi, Shahidah; Abdullah, Suhaila (IIUM Press, 2024)
INTRODUCTION: Recent breast cancer research has focused on tumour microenvironment (TME). Tumour-associated macrophages (TAMs) are the key players in TME as they provide pro-tumorigenic milieu for tumour progression and metastasis. These macrophages are primarily regulated by colony-stimulating factor-1 (CSF-1) secreted by breast cancer cells. This study investigated the association of localization of TAMs infiltration within breast carcinoma and CSF-1 expression by cancer cells with the pathological prognostic parameters. MATERIALS AND METHODS: TAMs were assessed in 128 cases of invasive breast carcinoma by CD163 immunohistochemical expression. The median TAM density in both the tumour nest and tumour stroma was utilized to classify TAMs into categories of low and high infiltration. The cancer cells were immunostained with anti-CSF-1 antibody and the staining intensity was evaluated as low or high expression. RESULTS: High nest and stromal TAMs were associated with higher tumour grades (p=0.005 and p=0.0001, respectively) whereas only high stromal TAMs showed significant association with negative oestrogen and progesterone receptors status (p=0.001 and 0.001, respectively); and triple-negative subtype (p=0.002). High CSF-1 expression was significantly associated with high stromal TAMs (p=0.031). High CSF-1 expression was associated with tumour grade and positive HER2 status (p=0.008 and 0.007, respectively). CONCLUSION: TAMs in tumour nest and stroma showed varying degrees of association with the clinicopathological parameters. High CSF-1 expression was associated with unfavourable prognostic parameters. Therefore, the evaluation of TAMs and CSF-1 expressions could potentially serve as prognostic markers and cellular targets for novel treatment modality in invasive breast cancers.